Western civilizations, their history and their culture - Lerner, Robert E.; Meacham, Standish; Burns, Edward McNall (New York : W. W. Norton, 1998)
This book is divided into seven parts: The dawn of history; The classical civilization of Greece and Rome; The Middle Ages; The early-modern world; The French and industrial revolutions and their consequences; The West at the world's center; and The emergence of a world civilization.
Keywords: Civilization; Western civilization; Civilization, Western; Europe -- Civilization